PENERAPAN TEORI PERKEMBANGAN MENTAL PIAGET PADA KONSEP KEKEKALAN PANJANG - Idrus Alhaddad (IKIP Siliwangi and I-MES, 2012)
According to the mental development of Piaget's theory, there are four stages of cognitive development in children, namely: 1) sensory phase motors, from birth until the age of about 2 years; 2) Phase pre operations, from the age of about 2 years to about 7 years; 3) stage of concrete operations, from the age of about 7 years to about 11-12 years; and 4) the stage of formal operations, from the age of about 11 years to mature.Each stage of mental development have a nature or characteristic of each. One of the characteristics that appear in the stage of concrete operations among which at this stage that children are beginning to understand the concept of eternity. Among the concept of eternity long (7-8 years). Of course it is aimed at children abroad where Jean Piaget did research, namely in the State Switzerland.The question is whether the stages of child development applies also to the children in our country. The results of our study showed that, there are children according to age are at the stage of concrete operations is not yet understand the concept of eternity long.